The Impact of Village Repositioning as Sub-district Units in Bungo Regency - Husni Husni; Aldri Frinaldi (Program Pascasarjana Universitas Negeri Makassar, 2023)
The change in the Law on Regional Government, specifically Law Number 23 of 2014, has resulted in significant impacts, particularly the transformation of villages into sub-district units. Issues that have emerged include the working relationship between village heads and sub-district heads, the organizational performance of villages after the regulatory change, and the performance of sub-district organizations in supervising villages. This research was conducted in Bungo Dani Sub-district, Bungo Regency, Jambi Province. The aim of this study is to examine the implementation impacts of the transformation of villages into sub-district units. The research method employed is qualitative research with a descriptive approach, as qualitative research can capture phenomena in detail and provide insights for the researcher. Data collection techniques involved interviews, observations, and documentation. The research utilizes the Manual Data Analysis Procedure (MDAP) to analyze the transcribed interview data collected in the field. The findings of this research are based on the Samoedra Wibawa policy impact evaluation theory. Overall, the research results indicate a satisfactory implementation, but some issues and obstacles were identified, such as poor communication between village heads and sub-district heads due to a lack of understanding of the prevailing regulations. In conclusion, the governance processes generally run well with a few challenges and issues. It is recommended that local governments take a more proactive role in providing education and knowledge to the officials in sub-districts and villages regarding the applicable regulations.